Investigating the construct of anxiety in relation to speaking skills among ESL tertiary learners - Chan, Swee Heng; Ain Nadzimah Abdullah,; Nurkarimah Binti Yusof, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Oral communication skills are a highly valued commodity. Part of the packaging is the exuding of confidence, which can be modulated by other mental states such as that of anxiety. Anxiety can be both good and bad and thus facilitating or debilitating, as a confidence booster or demotivator. Anxiety is worthy of investigation because it is a factor that influences communicative competence. Language anxiety can be defined along communication apprehension, test anxiety and fear of negative evaluation. Specifically, the study examines dimensions of language anxiety aligned to the major sub-constructs mentioned earlier. Data for this study is obtained through a survey questionnaire administered to 700 UPM students prior to an oral communication test. Findings suggest that most of the students experienced a medium level of oral communication apprehension, test anxiety and fear of negative evaluation. In the learning process, anxiety forms an important element that could determine language learning success. Thus, teachers must learn to identify anxiety and be able to enhance facilitating anxiety while reducing the negative. In this way, the teacher will have the awareness about the learning process of the oral skills defined along the construct of anxiety.